A Practical, Large-Scale Synthesis of p-(Difluoroiodo)toluene (p-TolIF2) - Tao, Jason; Murphy, Graham K. (Synthesis, 2019)
p-(Difluoroiodo)toluene (p-TolIF2) is a versatile fluorinating agent that acts as both a surrogate for elemental fluorine, and as a source of ‘electrophilic’ fluorine. Described here is a detailed three-step synthesis of p-TolIF2, carried out on a 50 mmol scale, that consistently provides high-quality product that is suitable for long-term storage. The reactions employ inexpensive, readily available starting materials and reagents, and uses the commodity chemical 48% aqueous HF as the source of fluorine atoms.
Keywords: hypervalent iodine; p-(difluoroiodo)toluene; fluorination; synthetic methodology; oxidation